Fabrication of ZIF-8 / polyimide mixed matrix membranes and their structural properties - Jusoh, N. (Asian Research Publishing Network, 2016)
In the present research, a series of mixed matrix membranes (MMMs) consisting of 6FDA-durene as polyimide phase and ZIF-8 as inorganic filler were synthesized and characterized. The loading of ZIF-8 in the polyimide phase were varied from 5 to 20 wt. The structural properties of the resultant membranes were studied using X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X-ray (EDX) Spectroscopy. The characterization results showed that excellent compatibility and good distribution of ZIF-8 in 6FDA-durene polyimide phase were observed even at higher ZIF-8 loading up to 20 wt. Â© 2006-2016 Asian Research Publishing Network (ARPN).